Peranan Kegiatan Kuliah Kerja Nyata (KKN) UPNVYK Dalam Media Literasi Digital Pada Masyarakat Pedesaan - Awang Hendrianto Pratomo (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
Increasing digital literacy is crucial in the age of digital transformation, especially in rural communities. Data from the Ministry of Communication and Informatics (KOMINFO) shows that Indonesia's Digital Literacy Index has seen improvement, but challenges persist, particularly in marginalized rural areas. To address this, the 77th batch of Kuliah Kerja Nyata (KKN) at UPN "Veteran" Yogyakarta has taken a strategic step towards empowering digital literacy in rural communities. This initiative focuses on four pillars of digital literacy: digital skills development, fostering a positive culture related to technology, promoting digital ethics, and ensuring digital safety. The KKN project involves college students who not only provide access to technology but also create an environment that encourages community participation in the digital era. In collaboration with UPN "Veteran" Yogyakarta, KOMINFO, and the Regent of Bantul, the KKN successfully implemented a digital literacy program in Karang Tengah Village, Bantul Regency, with the participation of 1,000 individuals. The program included activities such as socialization, door-to-door digital literacy, workshops, and a closing ceremony. The program effectively improved the community's digital skills, fostered a positive culture surrounding technology, instilled digital ethics, and promoted digital safety on social media platforms.